KEBERSYUKURAN DAN KEBAHAGIAAN PADA WANITA YANG BERCERAI DI ACEH - Dian Eriyanda; Maya Khairani (Universitas Katolik Soegijapranata, 2017)
The number of divorce cases in Aceh increases every year. With most divorce cases filed by the wife. In light of divorce, divorcées still needs a sense of gratitude to go on with life. Gratitude can manifest positive feelings such as happiness. This study aims to determine the correlation between gratitude and happiness on divorcées in Aceh. This study was done by quantitative approach with purposive sampling technique. The sample in this study are 247 divorcées. Data analysis using the Spearman test showed correlation coefficient of 0,650 with p < 0,10. The hypothesis was confirmed so it can be concluded that there's a significant positive correlation between gratitude and happiness on divorcées in Aceh. This shows that on divorcées in Aceh, the more grateful therefore the happier. The result of this study also shows that divorcées in Aceh falls under the high category for gratitude and happiness.